Comparing different definitions of prediabetes with subsequent risk of diabetes: An individual participant data meta-analysis involving 76 513 individuals and 8208 cases of incident diabetes - Lee, Crystal; Colagiuri, S.; Woodward, M.; Gregg, E.W.; Adams, R.; Azizi, F.; Gabriel, R.; Gill, T.K.; Gonzalez, C.; Hodge, A.; Jacobs, D.R.; Joseph, J.J.; et al. (BMJ PUBLISHING GROUP, 2019)
Objective: There are currently five widely used definition of prediabetes. We compared the ability of these to predict 5-year conversion to diabetes and investigated whether there were other cut-points identifying risk of progression to diabetes that may be more useful.